Level of knowledge about urinary incontinence and physiotherapeutic treatment among elderly women (Research, Society and Development, 2022)
Urinary incontinence is a public health issue that affects elderly women, however most of the elderly population is unaware of the role of physical therapy in improving this condition. This study aimed to investigate the level of knowledge about urinary incontinence (UI) and physical therapy among elderly women. It was an exploratory and quantitative study with women aged 60 years or over using an electronic form after disclosure and invitation on social networks. The sampling, therefore, was for accessibility and convenience, and the volunteers answered questions referring to sociodemographic characteristics, health status, life habits and obstetric data; and the 'Incontinence Quiz' questionnaire, which has questions about knowledge about Urinary Incontinence and Physiotherapeutic Treatment. Quantitative data were evaluated using descriptive and inferential statistics and presented in tables for better delineation of results. The prevalence of incontinent elderly women in the study was 38.2%, the chi-square test showed a significant association between having UI and the number of deliveries (p